2022
DOI: 10.1139/cjfas-2021-0141
|View full text |Cite
|
Sign up to set email alerts
|

Ecological responses to elevated water temperatures across invasive populations of the round goby (Neogobius melanostomus) in the Great Lakes basin

Abstract: Climate warming is expected to alter the distribution, abundance, and impact of non-native species in aquatic ecosystems. In laboratory experiments, we measured the maximum feeding rate and critical thermal maximum (CTmax) of an invasive Eurasian fish, the round goby (Neogobius melanostomus), acclimated to a range of temperatures (18–28°C) reflecting current and projected future thermal conditions for the nearshore Great Lakes. Fish were collected from four distinct populations along a latitudinal gradient fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 81 publications
(117 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, Lee and Johnson (2005) used fish from Lake Erie and Lake St. Clair, which are located ~ 3° south from our sampling location in the St. Lawrence River. A previous study testing the critical thermal maximum of adult round gobies from the St Lawrence River populations, including our Lake St. Louis population, found that (1) these fish had significantly lower thermal tolerances than goby populations from the lower Great Lakes, and (2) feeding rates of Lake St. Louis gobies peaked at 24°C, rather than 26°C (Reid and Ricciardi 2022). This same study recorded variable summer temperatures experienced by round gobies at different locations within the Great Lakes Basin, which could result in population‐level differences in thermal responses because recent thermal history could impact a population's ability to acclimate to novel conditions (Somero 2010; Reid and Ricciardi 2022).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Furthermore, Lee and Johnson (2005) used fish from Lake Erie and Lake St. Clair, which are located ~ 3° south from our sampling location in the St. Lawrence River. A previous study testing the critical thermal maximum of adult round gobies from the St Lawrence River populations, including our Lake St. Louis population, found that (1) these fish had significantly lower thermal tolerances than goby populations from the lower Great Lakes, and (2) feeding rates of Lake St. Louis gobies peaked at 24°C, rather than 26°C (Reid and Ricciardi 2022). This same study recorded variable summer temperatures experienced by round gobies at different locations within the Great Lakes Basin, which could result in population‐level differences in thermal responses because recent thermal history could impact a population's ability to acclimate to novel conditions (Somero 2010; Reid and Ricciardi 2022).…”
Section: Discussionmentioning
confidence: 89%
“…This decline may have been exacerbated by the limited amount of food offered in our experiment. Reid and Ricciardi (2022) observed reduced feeding in adults of the same population at higher temperatures, and juveniles might be even more susceptible to thermal stress. Under low food availability and warmer conditions, juvenile round gobies likely could not meet the energy demands to maintain growth.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The CT max of Restigouche and Miramichi salmon increased by ~0.5 and 1.2°C, respectively, for the +3°C warmer acclimation cycle, which is about the typical expected increase in CT max for every 3°C found in other fishes (0.9–1.2; Beitinger et al, 2000 ; Comte and Olden 2016 ; Morley et al, 2019 ). For some fishes under warm temperatures, CT max increased only slightly with warm acclimation ( Morrison et al, 2020 ; Reid and Riccairdi 2021 ), which could indicate that the fish is approaching its thermal ceiling and is unable to adjust CT max . Our data indicate that our temperature cycles were within the thermal breadth of performance for Atlantic salmon in both tested populations.…”
Section: Discussionmentioning
confidence: 99%
“…Following the acclimation period, a fixed number of prey (225 thawed chironomid larvae, Chironomus sp., previously kept frozen, mean total thawed mass 1.60 g ± 0.04SE). This prey abundance was chosen to ensure oversaturation of prey items in the tank by Round Goby and White Sucker [preliminary experiments unpublished, (Reid and Ricciardi, 2021)]. Once chironomids were introduced, feeding behaviour was recorded for 2 hours.…”
Section: Temperature Feeding Experimentsmentioning
confidence: 99%